2(x+4)-3=3(2x-3)+15

Simple and best practice solution for 2(x+4)-3=3(2x-3)+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+4)-3=3(2x-3)+15 equation:


Simplifying
2(x + 4) + -3 = 3(2x + -3) + 15

Reorder the terms:
2(4 + x) + -3 = 3(2x + -3) + 15
(4 * 2 + x * 2) + -3 = 3(2x + -3) + 15
(8 + 2x) + -3 = 3(2x + -3) + 15

Reorder the terms:
8 + -3 + 2x = 3(2x + -3) + 15

Combine like terms: 8 + -3 = 5
5 + 2x = 3(2x + -3) + 15

Reorder the terms:
5 + 2x = 3(-3 + 2x) + 15
5 + 2x = (-3 * 3 + 2x * 3) + 15
5 + 2x = (-9 + 6x) + 15

Reorder the terms:
5 + 2x = -9 + 15 + 6x

Combine like terms: -9 + 15 = 6
5 + 2x = 6 + 6x

Solving
5 + 2x = 6 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + 2x + -6x = 6 + 6x + -6x

Combine like terms: 2x + -6x = -4x
5 + -4x = 6 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + -4x = 6 + 0
5 + -4x = 6

Add '-5' to each side of the equation.
5 + -5 + -4x = 6 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = 6 + -5
-4x = 6 + -5

Combine like terms: 6 + -5 = 1
-4x = 1

Divide each side by '-4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| 30-10x=-7(x-6) | | 2x-6=59-11x | | 22-55+(85+65)=5 | | 25+3x=37 | | 6v-10=2v+2 | | 230x-25=440 | | 7x-7=x+29 | | 25x-230=440 | | c=38.51+0.50x | | 5x+2=-4(x-3) | | 6b+8a=9 | | 180=(20y-10)+2x | | 25x+330=440 | | 7+2.5h=19-4x | | 14=4h-6 | | 3(d-1)=12 | | 230x+25=440 | | 195=56-v | | -16x--2=46 | | 5x+86=11x-10 | | r^2=9r-18 | | 10=2+2j | | -13+10x=-63 | | 7+2.5x=19-4x | | 25x+230.00=440.00 | | 31=3(w+7)-8w | | 4x+4=-6x+24 | | 6x+5+67=180 | | 7(3y+2)=-2 | | -12=-x+3x | | 8(5x+10)=40x-5 | | 24+8(c-3)=7c+5 |

Equations solver categories